KAJIAN AKTIVITAS EKONOMI PELAKU SEKTOR INFORMAL DI KOTA DENPASAR (Studi Kasus Wanita Pedagang Canang Sari) - Desak Putu Eka Nilakusmawati (PIRAMIDA, 2009)
In a difficult economics condition, many woman have to take a part in to overcomeeconomic problems which they face. One of its alternative is involved into labour market,and trade is one of its choice. Because of the existence of opportunity in Denpasar City,many women overcome their economic problems and try to give contribution to theirhousehold income by selling canang.The aims of this research were: 1) to study about economics activity of woman ascanang sellers in Denpasar City; and 2) to analyse how far woman’s contribution ascanang sellers in improving their household economics resilience.Approach which is utilized in this research is survey method and depth interviewmethod. Research area elected by using purposeive method, that is in Denpasar City.While responder in this research is woman as canang sellers, and total responder to betaken 150 person. Datas collected by observation and interview to responder by usinginterview technique used questionnaire according to wanted of data. Data collected in fieldrepresent research variables: 1) Economic Activity of Responder; and 2) Contribution inEconomics of Household. Data analyse technique used descriptive qualitative to obtaineddata from result of interview and observation, while quantitative data analysis usedanalysis of statistics, that is descriptive statistics and inferential.Result of the research showed that mean of work duration of responder is 11,5 year,there are 17,3% responder representing new comer, because duration their involvement asnew canang seller just one until two year. Most responder have work duration ? 10 year,that is equal to 51,3%. Mean of work hours per week is 70 hour. Responder withoutassisted by family labour, predominated by 51,3%, constructively one person labour fromfamily, there are counted 39,3%. From 77 responder without family labour, there are 62person do by themselves without existence of family labour. Omzet per day from sellingcanang relatively high, that is Rp. 103.000. Mean of capital required per day is Rp.72.900,-, and mean of netto earning per day obtained by responder is Rp. 25.400. Meanpercentage of contribution of canang seller in this research is 35,79%. Ranged from 4,2%until 98,33%. Analysis of responder’s answer regarding the reason of them to involve asseller of canang, there are 86,0% responder which replying because reason of compulsionto work, reason of self actualization answered by 11,3% responder, while other reasonanswered by 2,7%.